Analysis of jet wall flow and heat transfer conveying ZnO-SAE50 nano lubricants saturated in Darcy-Brinkman porous medium - Ishak, Anuar; Khan, Umair; Zaib, Aurang; Waini, Iskandar; M. Sherif, El-Sayed; Pop, Ioan (MDPI, 2022)
The problem of 2D (two-dimensional) wall jet flow, along with heat transfer incorporated by nanofluid in a Darcy-Brinkman medium, while recognizing the requirement for efficient heating and cooling systems. Following the use of similarity variables, the resultant system of ODEs (ordinary differential equations) is solved using the well-known and efficient bvp4c (boundary-value problem of the 4th order) technique. The significance of physical quantities for the under-consideration parameters is illustrated and explained. The findings show that the nanoparticle volume fraction and porosity parameters decrease the velocity, but increase the temperature. In addition, the temperature uplifts in the presence of radiation effect. The suction parameter initially decreases and then increases the velocity near the surface, while the temperature declines.